Pemberdayaan Remaja Putri dalam Screening Anemia di Pesantren - Tina Yuli Fatmawati; Andicha Gustra Jeki; Maryam Novitasari; Liya Putri Rahmaniya (Prosiding Seminar Kesehatan Nasional, 2025)
Anemia is a common nutritional problem experienced by adolescent girls. Anemia-affected girls are at risk of developing anemia during pregnancy. Anemia also increases the risk of impaired concentration in learning and decreased academic achievement. The purpose of establishing the Anemia Ambassador Team is to improve the knowledge and skills of cadres about anemia and anemia screening. The Community Service activities were carried out from April to August 2025, with intensive mentoring conducted in July 2025 at the Al Hidayah Islamic Boarding School in Jambi City. The target of this community service was the 10 ORSADA CADRES of Al Hidayah Islamic Boarding School. The methods used were lectures, discussions, and questions and answers, pre-tests, and post-tests. The results of the activities showed The implementation of the Community Service Program (PkM) demonstrated that the formation of the Anemia Ambassador Team successfully improved ORSADA cadres' knowledge and skills regarding anemia, from understanding its causes, signs and symptoms, to prevention and management. Furthermore, cadres were able to conduct anemia screening in a more efficient and standardized manner. Strengthening peer cadres such as ORSADA Cadres has proven to be more effective in influencing adolescent behavior than a top-down approach, due to the sense of trust and emotional closeness